Manajemen Pembelajaran Anak Berkebutuhan Khusus Pada Sekolah Dasar Penyelenggara Inklusi - Nurdianti, Maya; Sowiyah; Nuraini, Siti; Nurwahidin, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem addressed in this study is that the learning management for students with special needs at SD Negeri 5 Metro Timur has not been optimal due to the absence of a Special Education Teacher, resulting in all learning processes being handled directly by classroom teachers. This study aims to describe the learning management for students with special needs in an inclusive elementary school, covering planning, organizing, implementation, and evaluation of learning. This research employed a qualitative method with a case study approach, using interviews, observations, and documentation techniques. The study was conducted at SD Negeri 5 Metro Timur, with the principal and teachers who handle students with special needs as the research subjects. The results indicate that learning planning is carried out through initial identification of the abilities and characteristics of students with special needs; learning organization is implemented by assigning classroom teachers as companions for these students; learning implementation is conducted flexibly through simplified instructional materials; and learning evaluation is carried out in a simple manner through daily observations, adapted assignments, and follow-up actions such as repetition of materials or additional tasks.